Investigation of Bacillus anthracis spore survival in soils from Kruger National Park in South Africa and Etosha National Park in Namibia - Van Heerden, Henriette (University of Pretoria, 2023)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2022.